Updated bird list of Lagoa do Peixe National Park, one of the most important South American wetlands - Delfino, Henrique Cardoso (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
The Lagoa do Peixe National Park is an important federal protected area for migratory and resident birds located on the middle coast of the state of Rio Grande do Sul, southern Brazil. Nevertheless, the ornithological fauna of the Lagoa do Peixe National Park is still underestimated. The main goal of this article is to review all available ornithological records and update the list of species that occur in the Park. Furthermore, the species with confirmed records in the National Park were also classified based on their occurrence, diet, main habitat associated, conservation status, and populational trends, aiming to fully characterize the ornithological fauna of the Protected Area. The primary and secondary lists recorded 349 species for the area, including 74 migratory and 13 under some level of threat. Invertebrates represented the main prey item of the bird species analyzed. Most bird species were associated with forest environments, with a relevant number of species exclusively dependent of wetland and coastal habitats. The number of species recorded reinforces the importance of the area for the conservation of birds in South America. Furthermore, the list can be an important tool for the development of conservation and management actions, environmental education, and science communication.
Keywords: Conservation; Mostardas peninsula; Ornithology; Species list; Tavares